Pengaruh Variasi Konsentrasi Polivinil Pirolidon K-30 sebagai Pengikat dalam Pembuatan Oral Fast Dsissolving Tablet Domperidon Base - Deny budi legowo; Riski Ramadhan; Erna Fitriany; Indah Tri Lestari (AFAMEDIS, 2021)
Domperidone base as anti-nausea or vomiting drug mostly available in conventional tablets forms has weakness in swallowing tablets and requires drinking water. Oral fast dissolving tablets are a solution to this problem. Oral fast dissolving tablets with variations in the concentration of PVP K-30 to determine effect of the tablet physical quality test and good physical quality results. The wet granulation method was used to improve the flow properties by mixing the binder mucilago with the inner phase. Test of physical quality of tablets, weight uniformity, size uniformity, hardness, friability, disintegration time, and unifomity of content. The results showed a significant difference in friability and disitegration time. The conclusion based on the results of the study showed that the variation in the concentration of PVP K-30 on the difference in the physical quality test of tablets and the 2% concentration of PVP K-30 gave good results